Slovenian fermented milk with probiotics - Nada VAHČIĆ; Mirjana HRUŠKAR (Acta Agriculturae Slovenica, 2000)
The concept of functional foods and probiotics is a novelty in former Eastern block. The Croatian and Slovenian dairy industries are the first that launched probiotic. In this work, samples of probiotic fermented milks purchased from Slovenian market were stored within 25 days at three different temperatures (4° C, 20° C, 37° C), and changes in acetaldehyde, ethanol and diacetyl were determined. Above chemical compounds have a high impact on the desired product flavour. At the same time sensory evaluation was carried out. Acetaldehyde and ethanol concentration were determined by aldehyde dehydrogenase and alcohol dehydrogenase methods. Diacetyl was measured by modification of the Hill’s colorimetric method. Sensory analysis was conducted by five member panel, using a scoring system with weighted factors in the 20-point scale. The concentration of these flavour compounds changed during storage depending on duration and temperature in depot. Acetaldehyde content decreased at each temperature level during 25-days storage. Diacetyl and ethanol content increased with duration at all temperature levels. Sensoric quality decreased with duration and was closely related to changes in the content of aroma compounds. Changes of all investigated parameters were pronounced on higher temperature levels. Thus, there were no significant changes during the refrigerated storage at 4°  C while at the other two temperature levels results pointed out significant differences between the values before and after storage.